ANALISA VARIASI TINGGI KELUARAN TABUNG KOMPRESOR TERHADAP UNJUK KERJA POMPA HIDRAM - Suparman Ahmadi; Rudy Sutanto; Arif Mulyanto (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
Water is one factor that is very important and necessary in the life of living creatures. Therefore, water should be available whenever and wherever in sufficient number, time, and it’s quality. The distribution of water in the plateau required an environmentally friendly tool and lower of operational cost. Hydraulic Ram (Hydram) pump is a pump which does not require external energy as the main driving force. This research would observe the effect of discharge input‘s variation and high variation of the compressor tube output (Air Chamber) toward the efficiency resulting.The specifications of Hydram pump which is used in this research is a 3-inch compressor tube (Air Chamber) with 60 cm of height. On the compressor tube there are five high variations output with 10 cm range in each pump’s body. The high levels of water used is 6 meter from the pump and the high water lift (output) used is 9,2 meter. Whereas, the parameter measured in this research are discharge input, discharge output, and the efficiency.The research result shows that the variation in output which produces high output discharge is greatest at 10 cm high output is 102,24 mℓ/s for input variations discharge 12421,63 mℓ/s, while the output of the lowest discharge generated by high output 50 cm which is 42,08 mℓ/s for input variations discharge 1730,10 mℓ/s. Whereas the highest efficiency that is 5,084 % higher output obtained from 10 cm to 1730,10 mℓ/s discharge input and the lowest efficiency is 1,023 % derived from 50 cm high output with input discharge 12421,63 mℓ/s.